STRATEGI PENERAPAN POLA TANAM BERGILIR PADA KELOMPOK TANI (Studi Kasus: Kelompok Tani “Taruna Jaya” Di Desa Matang Setui, Kecamatan Langsa Timur, Kota Langsa) - Devi Yanti Rizky; Supristiwendi; Thursina Mahyuddin (Jurnal Cakrawala Ilmiah, 2023)
This research took place in Matang Setui Village, east langsa district, langsa city. The purpose of this study was to detemine the internal factors and external factors in the appliction of the rotational cropping pattern to the taruna jaya farmer group and to determine the strategic priorities in the application of the rotational cropping pattern ti the taruna jaya farmer group. The research method in this study is a case study method where the research subject is the taruna jaya farmer group. The data collection method used descriptive and analytic methods with primary and secondary data. Primary data was obtained through direct interviews with the parties concerned using a list of questions or questionnnaires. And lso using secondary data obtained from agencies related ti the research. The samples in this study were 5 members of te farmer group and 5 expert samples. The analytical method used in this research is SWOT (strength, weakness, opportunities, threat) analysis. The result showed that the alternative strategies that can be applied in developing a business based on the SWOT matrix get 4 alternative strategies, namely SO strategy, ST strategy, WO strategy, and WT strategy. The IE matrrix explains that the taruna jaya farmer group is in quadrant I. Based on the QSPM analysis, the result of the SO strategy that can be applied to the taruna jaya farmer group are implemeting the right rotational cropping pattern by consulting with agricultural extension workers for the selection of suitable plant types to prioritize ll planted crops so that the results are optimal in order to stabilize and increase the income of farmer group members.